2017
DOI: 10.1002/oby.21820
|View full text |Cite
|
Sign up to set email alerts
|

Childhood body mass index and development of type 2 diabetes throughout adult life—A large‐scale danish cohort study

Abstract: Childhood BMIs below average are not associated with type 2 diabetes, whereas childhood BMIs above average are strongly associated with type 2 diabetes in adulthood, corresponding to excess risks even at levels below international definitions of overweight. The associations are stronger in women than men but are not affected by birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
51
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 33 publications
1
51
2
Order By: Relevance
“…Moreover, a fast growth in height between ages 7 and 15 years was associated with adult type 2 diabetes in this population . During childhood, height is positively correlated with birthweight and adiposity and we previously found that childhood body mass index (BMI; kg/m 2 ) is associated with adult type 2 diabetes . Therefore, the association between childhood height and type 2 diabetes may change depending on these factors.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Moreover, a fast growth in height between ages 7 and 15 years was associated with adult type 2 diabetes in this population . During childhood, height is positively correlated with birthweight and adiposity and we previously found that childhood body mass index (BMI; kg/m 2 ) is associated with adult type 2 diabetes . Therefore, the association between childhood height and type 2 diabetes may change depending on these factors.…”
mentioning
confidence: 75%
“…16 During childhood, height is positively correlated with birthweight and adiposity 17 and we previously found that childhood body mass index (BMI; kg/m 2 ) is associated with adult type 2 diabetes. 18 Therefore, the association between childhood height and type 2 diabetes may change depending on these factors. Furthermore, the association between BMI and type 2 diabetes is non-linear and potentially stronger for women than men.…”
mentioning
confidence: 99%
“…Breastfeeding may have protective effects against later obesity in the child, and more so the longer the duration of breastfeeding although it remains controversial (Brion et al, ; Harder, Bergmann, Kallischnigg, & Plagemann, ; Horta, Loret de Mola, & Victora, ). Given clear links between body mass index (BMI) in childhood and adulthood and type 2 diabetes (Whitlock et al, ; Zimmermann et al, ), it is possible that breastfeeding reduces the risk of type 2 diabetes in adulthood through an inverse association with BMI.…”
Section: Introductionmentioning
confidence: 99%
“…Given clear links between body mass index (BMI) in childhood and adulthood and type 2 diabetes (Whitlock et al, 2009;Zimmermann et al, 2017), it is possible that breastfeeding reduces the risk of type 2 diabetes in adulthood through an inverse association with BMI.…”
mentioning
confidence: 99%
“…In paediatric populations, obesity strongly associates with alterations in glucose metabolism, and impaired glucose metabolism and IR are observed not only in adults, but also in a large fraction of children with obesity [3, 4]. Furthermore, as increased BMI during childhood strongly correlates with increased risk of developing type 2 diabetes in adulthood [5], it is of great importance to identify risk factors potentially influencing or even mediating the link between childhood obesity and adult type 2 diabetes. Examination of factors predisposing to IR in clinical subsets of children who are overweight or obese is thus particularly relevant.…”
Section: Introductionmentioning
confidence: 99%